Бережок: стихи и рассказы / Виталий Коржиков - Коржиков Виталий Титович (Малыш, 1989)
Экземпляры: ф.2 (20100927) / Инвентарный номер: 96295 / Цена: 15 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: К 66 / ББК: 84(2Рос=Рус)6